Perlindungan Hukum Komprehensif bagi Anak Jalanan di Indonesia: Analisis Kritis Implementasi Undang-Undang No. 35 Tahun 2014 dalam Perspektif Kriminologi dan Hak Asasi Anak, dengan Studi Kasus di Kota Kendari - Rahayu Kojongian (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
This article critically examines the implementation of Law No. 35 of 2014 on Child Protection in Indonesia, focusing specifically on the challenges and strategies for protecting the rights of street children, with a particular emphasis on the context of Kendari City. Using a normative legal and socio-legal research approach, combined with a criminological perspective on vulnerability and exploitation, this study analyzes the effectiveness of the existing legal framework, educational interventions, and social support mechanisms. Key findings reveal that despite a strong legal foundation, significant gaps remain in the practical fulfillment of street children's rights due to socio-economic determinants, inadequate resource allocation, and coordination complexities. The article highlights the crucial role of non-formal education and victim-centered approaches in addressing child criminal exploitation. Comparative insights from international standards, such as the UNCRC and restorative justice principles, underscore the challenges of universal implementation while offering pathways for improved protection. Recommendations include strengthening inter-agency collaboration, expanding tailored education programs, and fostering greater community engagement to ensure a more just and protective environment for all children.